African American Women and Prenatal Care: Perceptions of Patient-Provider Interaction - Dahlem, Chin Hwa Y. (West J Nurs Res, 2014)
Poor patient-provider interaction among racial/ethnic minorities is associated with disparities in healthcare. In this descriptive, cross-sectional study, we examine African American women’s perspectives and experiences of patient-provider interaction (communication and perceived discrimination) during their initial prenatal visit and their influences on perceptions of care received and prenatal health behaviors. Pregnant African American women (n=204) and their providers (n=21) completed a pre and post-visit questionnaire at the initial prenatal visit. Women were also interviewed face to face at the subsequent return visit. Women perceived high quality patient-provider communication and perceived low discrimination in their interaction with providers. Multiple regression analyses showed that patient-provider communication had a positive effect on trust in provider (p <.001) and on prenatal care satisfaction (p <.001) but not on adherence to selected prenatal health behaviors. Findings suggest that quality patient-provider communication improves the prenatal care experience for African American women.